Ordinary Things: A Reflection on Race and Capital in the Pandemic - Parker, Lana (Journal of the Canadian Association for Curriculum Studies, 2022)
In response to the race-based, capitalist logics further exposed during the pandemic, I engage in poetic inquiry by weaving the words of Arundhati Roy in a multimodal Vox Justitia. I begin with brief rationale for the inquiry, noting that the pandemic has sharpened the harms of racism and capitalism, and has exposed the fragility of contemporary democracy. I then describe why poetic inquiring in general, and a Vox Justitia in particular, engaged through the writing of Arundhati Roy, offer a useful way to grapple with this moment. Finally, I proceed through the five movements of my Vox Justitia, employing images, news headlines, and excerpts from Roy’s writing, to contextualize my poetic analysis.